PENGARUH PASSION TERHADAP PERILAKU PROKRASTINASI AKADEMIK MAHASISWA - Virgie Nathania; Monika Monika (Fakultas Psikologi Universitas Tarumanagara, 2023)
Academic procrastination is the behavior of deliberately delaying assignments until the submission deadline, even though they already know the impact of the delay. With many tasks that students have, it can increase the tendency of delaying behavior to carry out other activities that students prefer. An activity that is highly liked by an individual is called Passion. Students tend to delay their assignments by doing other activities they like (for example playing games). This study discusses the role of passion that students have for an activity on academic procrastination behavior in students. The purpose of this study is to examine how big the role of passion is in academic procrastination. The target participants are students studying at universities in Jakarta. The research method used is non-experimental with a correlational type. The number of participants obtained from this study was 230 students spread across various universities in Jakarta using the convenience sampling method. The measuring instruments used in this study were the Passion Scale and the Academic Procrastination Scale. Regression analysis using SPSS version 26.0 shows that passion has a role of 2.5% (r = 0.159 / sig. = 0.016) in academic procrastination. The regression analysis between obsessive passion (OP) and academic procrastination shows that OP has a role of 5.5% (r = 0.235 / sig. = 0.000) on academic procrastination.